GE_GERICHTE P/19166/2013 vom 21. Februar 2017 - GE Cour de justice (2017)
VOIES DE FAIT ; TORT MORAL ; ORDONNANCE PÉNALE ; CLASSEMENT DE LA PROCÉDURE ; NOTIFICATION DE LA DÉCISION ; DOL ÉVENTUEL | CP12.2 CP126 CP52 CPP352 CPP353.3 CO47 CPP9.1 CPP355 CPP319 CPP80.2 CPP81 CPP322 CPP321